Tax Policy Reforms for Sustainable Development: Assessing Carbon Taxes and Environmental Compliance - Agus Rohmat Hidayat (Journal of Taxation Insights Policy Practice, 2025)
Carbon taxes are one of the most effective tools for promoting sustainable development. This study aims to assess the effectiveness of carbon tax policies in promoting environmental compliance and sustainable development across diverse contexts. The study employs a mixed-methods research design, combining both quantitative and qualitative approaches. Data was gathered from 20 countries that have implemented carbon taxes, focusing on emission reductions, carbon tax rates, and economic indicators. The results show that countries with higher carbon taxes see greater reductions in emissions without significant negative impacts on economic growth. The findings provide a blueprint for designing effective carbon taxes that align with sustainable development goals, encouraging governments to implement carbon taxes as a catalyst for green growth.